Performance evaluation of starfive visionFive V1 board - Kam, Kai Heng (2023)
The concept of a single board computer, as the name implies, involves a functional computer built on a motherboard with a CPU, RAM, and I/O devices, similar to a regular computer. Single board computers are becoming increasingly popular for Internet of Things (IoT) applications due to their affordability, energy efficiency, and ease of portability. One emerging instruction set architecture (ISA) is RISC-V, which is an open-source chip architecture designed to optimize power and performance for modern workloads such as IoT, artificial intelligence, and machine learning. This research aims to explore the performance advantages offered by the RISC-V ISA by benchmarking it against popular single board computers such as the Raspberry Pi (RPi), which is based on the ARM ISA. However, as RISC-V is a relatively new architecture, there are challenges to overcome in terms of compiler optimization, operating system and library support, and debugging tools. The main outcome of this research is to provide insights to developers regarding the performance advantages and benefits offered by the RISC-V ISA. The success of this project will contribute to increased awareness and trust in the VisionFive V1 Board among the community. Developers can leverage the performance advantages of this board for their applications, ultimately benefiting the broader community.